Numerical experiments on neutron yield and soft x-ray study of a ∼100 kJ plasma focus using the current profile fitting technique - Ong, S. T.; Chaudhary, K.; Ali, J.; Lee, S. (IOP Publishing, 2014)
Numerical experiments using the Lee model were performed to study the neutron yield and soft x-ray emission from the IR-MPF-100 plasma focus using the current fitting technique. The mass sweeping factor and the current factor for the axial and radial phase were used to represent the imperfections encountered in experiments. All gross properties including the yields were realistically simulated once the computed and measured current profiles were well fitted. The computed neutron yield Yn was in agreement with the experimentally measured Yn at 20 kV (E0 ∼ 30 kJ) charging voltage. The optimum computed neutron yield of Yn = 1.238 × 109 neutrons per shot was obtained at optimum physics parameters of the plasma focus operated with deuterium gas. It was also observed that no soft x-rays were emitted from the IR-MPF-100 plasma focus operated with argon gas due to the absence of helium-like and hydrogen-like ions at a low plasma temperature (∼0.094 keV) and axial speed (8.12 cmμs−1). However, the soft x-ray yield can be achieved by increasing the charging voltage, using a higher ratio of outer anode radius to inner anode radius c or shorter anode length z0, or using neon as the operating gas.